Actions speak louder than words: Environmental law enforcement externalities and access to bank loans - Wu, Xiting; Luo, Le; You, Jiaxing (Journal of Banking & Finance, 2023)
By exploiting the staggered city-level establishment of specialized environmental courts in China as exogenous shocks and using a difference-in-differences research design, we find that an increase in the efficiency of environmental enforcement leads to a decrease in companies’ access to bank loans. The channel tests show that these same shocks lead to an increase in environmental litigation, operational and reputational risk. The cross-sectional analyses also reveal consistent evidence. Collectively, our findings suggest that the environmental mandate has important externalities for bank lending decisions, indicating that the costs of environmental enforcement go beyond reducing environmental pollution.